2012
DOI: 10.3892/or.2012.1793
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor trichostatin A induces cell cycle arrest and apoptosis in colorectal cancer cells via p53-dependent and -independent pathways

Abstract: Abstract. Many chemotherapeutic agents induce apoptosis via a p53-dependent pathway. However, up to 50% of human cancers have p53 mutation and loss of p53 function. Histone deacetylase inhibitors (HDACIs) are emerging as a potentially important new class of anticancer agents. Here, we report that, Trichostatin A (TSA), a pan-HDAC inhibitor, could induce G2/M cell cycle arrest and apoptosis in both colorectal cancer cell lines with wild-type p53 (HT116 cells) and mutant p53 (HT29 cells), although HCT116 cells h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…PRI-2205 slightly decreased only PI positive cells, but did not affect caspase-3 or p-53 positive cells as compared to 5-FU alone. HT-29 possessed mutated p53 (67) and, according to recent studies, a functional and physical interaction between mutated p53 and the vitamin D transcriptional regulatory pathway exists. This interaction lies in the cooperation between mutated p53 with 1,25(OH) 2 D 3 to elicit an anti-apoptotic state (68).…”
Section: Discussionmentioning
confidence: 99%
“…PRI-2205 slightly decreased only PI positive cells, but did not affect caspase-3 or p-53 positive cells as compared to 5-FU alone. HT-29 possessed mutated p53 (67) and, according to recent studies, a functional and physical interaction between mutated p53 and the vitamin D transcriptional regulatory pathway exists. This interaction lies in the cooperation between mutated p53 with 1,25(OH) 2 D 3 to elicit an anti-apoptotic state (68).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we delineated p53-dependent and -independent activities of HDACi and, in part, resolved the controversies (Vrana et al , 1999; Huang et al , 2000; Ruefli et al , 2001; Yu et al , 2002; Henderson et al , 2003; Insinga et al , 2005; Joseph et al , 2005; Kim et al , 2006; Sonnemann et al , 2006; Lindemann et al , 2007; Condorelli et al , 2008; Ellis et al , 2009; Hacker et al , 2011; Bajbouj et al , 2012; Meng et al , 2012) over the impact of p53 on HDACi-driven effects. As general bottom line, we have shown that HDACi accomplish the ultimate goal of cancer therapy, the demise of malignant cells, independent of the tumour's p53 status.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of works addressing this issue point to a largely p53-independent action of HDACi (Vrana et al , 1999; Huang et al , 2000; Ruefli et al , 2001; Yu et al , 2002; Insinga et al , 2005; Sonnemann et al , 2006; Lindemann et al , 2007; Ellis et al , 2009). Other studies, however, suggest an essential role of p53 in the response of tumour cells to HDACi treatment (Henderson et al , 2003; Joseph et al , 2005; Kim et al , 2006; Condorelli et al , 2008; Hacker et al , 2011; Bajbouj et al , 2012; Meng et al , 2012). These inconsistent observations may in part be due to methodological differences, but they may also be due to the use of different HDACi or divergent HDACi-induced effects examined.…”
mentioning
confidence: 98%
“…p53 is an important protein involved in apoptosis and has been shown to participate in cell cycle regulation (17,18). In the present study, the mRNA and protein expression levels of p53 were investigated in the chorionic villus (placental) tissues of females with URSA by qPCR and immunohistochemical analysis.…”
Section: Discussionmentioning
confidence: 99%